Performance of a table vibration type coffee grading machine - Sukrisno Widyotomo; Sri Mulato (Indonesian Coffee and Cocoa Research Institute, 2005)
One of important coffee beans quality is the size uniformity. To confirm with the standart requirement, coffee beans have to be graded before being traded. Until now, grading process is still carried out fully manual, so that the grading cost is very expensive about 40% of total processing cost. Meanwhile, shortage of skill workers is as a limiting factor of the process. Therefore, machine for grading coffee beans is good alternative for grading cost. Indonesian Coffee and Cocoa Research Institute has designed a table vibration type coffee grading machine for grouping of coffee beans in order to consistent quality and reduce grading cost. The machine has dimension of 272 cm length, 126 cm height, and 144 cm width. The machine has three primary components, i.e. grader table, combustion engine, and beam. The machine has three kinds of grader table that each grader table has different holes size, i.e. 7 mm x 7 mm for top grader table, 5 mm x 5 mm for axle grader table, and 4 mm x 4 mm for bottom grader table. Each grader table has dimension of 206 cm length, 105.5 cm height, and 14 cm width. The grading mechanism is by vibration grader table with the power source 5.5 HP combustion engine. The results shown that the outlet are in farms of three grades of coffee beans with connected to each compartement. Assessment of the grading machine reveals that the optimum capacity of 1,406 kg/hour reached when the speed 2,600 rpm and the angle 10O. Economic analysis showed that operational cost for grading one kilogram Robusta coffee beans with moisture content 13—14% wet basis is Rp 7.17.Key words : grading, coffee, quality, vibration table.